Increasing Physical Literacy in Pencak Silat Athletes: Two-Months Peer Teaching Model Program in COVID-19 - Abdurrohman Muzakki; Edi Setiawan; Mashuri Eko Winarno; Ruslan Abdul Gani; Novi Yanti; Bangbang Syamsudar; Martin Hofmeister (OVS LLC, 2023)
Study purpose. This study aims to investigate the effect of the peer teaching model on improving the physical literacy of pencak silat athletes. Materials and methods. This study applied a mixed method. Participants were pencak silat male athletes (N=30) who studied at elementary schools in Cianjur district (Indonesia). Participants were divided into an experimental group (n=15) that carried out the peer teaching model and a control group (n=15) that carried out daily teaching routines without participating in any activities. After implementing the peer teaching model, 15 participants were interviewed about the implementation of peer teaching in school model and the benefits of peer teaching. The quantitative research instrument involved physical literacy-movement competence, cognitive and affective domains. Meanwhile, the qualitative research instrument involved in-depth interviews for 30 minutes. Analysis of quantitative data used IBM SPSS. Analysis of qualitative data used thematic analysis. Results. The quantitative study results showed that there was a significant increase in physical literacy in the experimental group (p<0.05) but there was no increase in the control group (p>0.05). The qualitative study results showed that most of participants gave diverse perceptions and all agreed that the peer teaching model could improve the physical literacy of athletes with poor condition. Conclusions. This study concluded that peer teaching is an alternative teaching that can be used during COVID-19 to improve the physical literacy of pencak silat athletes.